INFLUENCE ELECTRONIC WORD OF MOUTH AND CONSUMER PERCEPTION TOWARDS PURCHASING DECISIONS AT SAHADJA MIE DEPOT, MALANG CITY - Qothrun Nada; Anggi Martiningtyas Januwati Saputri; Teti Setiawati; Nunung Nurjanah (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
The development of social media, particularly Instagram, has opened new opportunities for culinary promotion through Electronic Word of Mouth (e-WOM) activities. Informal communication among users regarding culinary experiences is now often packaged in the form of review content and promotions by influencers. However, as influencer-driven promotions increase, issues arise regarding consumer perceptions, which begins to question the authenticity of reviews, as they are perceived to resemble commercial advertisements. This phenomenon impacts consumer trust and purchasing decisions, specifically in culinary enterprises like Mie Sahadja Depot located in Sigura -gura . Based on this, the study aims to analyze the influence of Electronic Word of Mouth on Instagram on purchasing decisions at Depot Mie Sahadja in Malang City, as well as how consumer perceptions influence purchasing decisions, and whether both variables simultaneously affect consumer purchasing decisions. The findings of this research reveal that both Electronic Word Of Mouth (e-WOM) and consumer perceptions individually exert a significant impact on purchasing decisions at Mie Sahadja Depot, Malang City. This finding aligns with previous research stating that e-WOM on social media, particularly Instagram, plays a role in shaping consumer purchasing interest by providing easily accessible information and reviews. Additionally, positive consumer perceptions of product quality, service, and price also serve as factors reinforcing purchasing decisions. Simultaneously, these two variables complement each other, where information from e-WOM reinforces consumer perceptions, ultimately driving them to make a purchase.